Components of automated intellectual systems supporting decisions at the stage of operation and equipment diagnostics of nuclear power units - Yefimov, О.V.; Pylypenko, М.М.; Potanina, Т.V.; Yesypenko, Т.О.; Kavertsev, V.L.; Harkusha, Т.А. (Вопросы атомной науки и техники, 2020)
The results of studies of parameters, characteristics and performance of NPP units by mathematical modeling methods using computer–integrated technologies for their implementation, which allow to simulate many functional states of systems and equipment of NPP units during the simulation experiment are presented. The general structure of interaction of blocks of software complex for analysis of efficiency of work and parametric diagnostics of NPP units with WWER is developed. The structure of the block of programs of parametric diagnostics of equipment of NPP units is presented. The essence of methods and approaches of parametric diagnostics of power unit equipment is considered. Представлено результати досліджень параметрів, характеристик та показників роботи енергоблоків АЕС методами математичного моделювання з використанням комп’ютерно–інтегрованих технологій їх реалізації, які дозволяють імітувати в процесі імітаційного експерименту множину функціональних станів систем та устаткування енергоблоків АЕС. Розроблено загальну структуру взаємодії блоків програмного комплексу для аналізу ефективності роботи і параметричної діагностики енергоблоків АЕС з ВВЕР. Представлено структуру блоку програм параметричної діагностики устаткування енергоблоків АЕС. Розглянуто сутність методів та підходів параметричної діагностики устаткування енергоблоків. Представлены результаты исследований параметров, характеристик и показателей работы энергоблоков АЭС методами математического моделирования с использованием компьютерно–интегрированных технологий их реализации, которые позволяют имитировать в процессе имитационного эксперимента множество функциональных состояний систем и оборудования энергоблоков АЭС. Разработана общая структура взаимодействия блоков программного комплекса для анализа эффективности работы и параметрической диагностики энергоблоков АЭС с ВВЭР. Представлена структура блока программ параметрической диагностики оборудования энергоблоков АЭС. Рассмотрена сущность методов и подходов параметрической диагностики оборудования энергоблоков.